Social media monitoring dashboard for university - Tan, Dicken (2020)
As social media has been penetrated our lives, analysis of data becomes essential in order to allow people to make well informed decisions. In this project, data related to education is important for the people mainly management of universities or higher education institutions. Hence, the collection of data to perform analysis for better management decision thinking is displayed on a dashboard by implementing a business intelligence. The project objectives of this project are to visualise all social media data at a glance in a dashboard and then monitor the data that is being extracted and analysed as these data is targeted to meet the requirements of users. The implementation of the dashboard is performed from scratch which starts with extraction of social media data from various platforms or sources and stored the data in database management system and finally the data is retrieved from the management system with SQL queries to display data at the dashboard. This university dashboard could show various types of tables and visualisation although there are some challenges and restrictions on overall design due to inadequate of time and data complexities. In short, the dashboard consists of few tabs which basically could be filtered based on name of university, type of university and date of the data being published. Some analysis will be displayed to allow users to view the sentiments and classification of content. Future work could mainly focus on collecting data from other social media platforms, performing trend analysis and more visualisation that is interesting to be shown.